Prevalence of Bandemia in Respiratory Viral Infections: A Pediatric Emergency Room Experience - Estela Noyola; Asif Noor; Nicole Sweeney; Joshua Chan; Rahul Ramesh; Rose Calixte; Rose Calixte; Leonard R. Krilov (Frontiers Media S.A., 2020)
Objective: The aim of this study was to examine the prevalence of bandemia in confirmed respiratory viral infections in febrile infants and children presenting to the emergency department.Methods: An observational retrospective study from January 1, 2016, through December 31, 2016, was conducted in patients between the ages of ≥ 1 month and ≤ 5 years presenting to the emergency room with fever and who had a complete blood cell count performed. Patients were separated into seven groups based on the type of respiratory viral infection. Inclusion criteria strictly counted children with viral infections and absence of clinical and laboratory evidence of a bacterial coinfection.Results: A total of 419 patients had a documented viral infection. A significant proportion of these children were found to have bandemia; children with adenovirus (17%), respiratory syncytial virus (RSV) (14.9%), human metapneumovirus (hMPV) (13%), and parainfluenza virus (7.9%) had the highest prevalence when the cutoff for bandemia was set at 10%. The prevalence increased to 35.3, 30.9, 40.3, and 15.8% for adenovirus, RSV, hMPV, and parainfluenza virus, respectively, when this cutoff was lowered further to 5%.Conclusion: Band neutrophils are detected frequently in confirmed respiratory viral infections particularly during early stages.